ANALISIS RISIKO HARGA JUAL EMAS DAN INVESTASI SAHAM ANTAM MENGGUNAKAN EXPECTED SHORTFALL PADA MASA PANDEMI COVID-19 - Dwi Sulistiowati; Maya Sari Syahrul; Ilham Dangu Rianjaya (Jurnal Matematika, Statistika dan Komputasi, 2021)
The Covid-19 pandemic caused the price of gold produced by PT Aneka Tambang (Antam) to experience a high increase following the world gold price, while stock investment decreased. Measuring risk is significant in financial analysis; this is related to investment funds, which are quite large and narrow about public funds. This study analyzes the risk data on Antam gold price and Antam stock closing price with an estimated Shortfall (ES). The method used to measure the risk of investing in stocks is ES. ES is the expectation of a conditional loss that exceeds Value at Risk (VaR). To compute ES data showing deviations from normality and Cornish-Fisher expansion. The volatility measurement model used is the autoregressive conditional heteroskedasticity (ARCH) and generalized ARCH (GARCH) model.This study found that the ES value of Antam gold price was smaller than Antam stock price.